Pengaruh Terpaan Iklan Frestea di Televisi dan Terpaan Komunikasi Word of Mouth terhadap Keputusan Pembelian Produk Frestea - Eris Ariesda, Teo; Luqman, yanuar (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2020)
The purpose of this study was to understand the effects of Frestea advertising exposure on television and word of mouth communication exposure towards purchase decisions of Frestea products. Theory that was used in this research are Advertising Exposure Theory and Buyer Information Environment Theory. Sampling techniques that being used is non-probability sampling with 60 total samples, man or woman domiciled in Semarang Cit, aged 17 – 30 years, had seen Frestea advertisement on television, and had interact through word of mouth about Frestea products. The analysis data used is simple linear regression. The results of the study indicates that advertising exposure and word of mouth communication exposure had a very significance effects to purchase decisions of Frestea products.